Fungal brain abscesses caused by Acremonium species - Hamdy Ibrahim; Mostafa ALfishawy; Attaa Ali; Safwat Abdel Maksod; Magdy Khorshed; Hanan Rady; Ahmed Alsisi; Adel Mohamed; Omar Alkassas; Marwa Haron; Suzan Saied (SpringerOpen, 2023)
Abstract Unusual fungal agents that exist environmentally as saprophytes can often lead to opportunistic infections, hyalohyphomycosis is a group of fungal infections caused by fungi characterized by hyaline septate hyphae and can infect both immunocompetent as well as immunocompromised patients, and Acremonium has drawn the attention of clinicians and microbiologists, as a potential pathogen in patients with and without underlying risk factors. It has also been increasingly implicated in systemic fungal diseases. Herein, we describe a case presentation of an immunocompromised patient with fungal brain abscesses due to Acremonium species.